1985
DOI: 10.1177/014107688507800705
|View full text |Cite
|
Sign up to set email alerts
|

Low-Dose Guar Improves Diabetic Control

Abstract: Twenty diabetic outpatients (12 non-insulin-treated and 8 insulin-treated) were given guar granulate in a dose of 10 g daily for two months in order to study the effect on glycaemic control and lipid levels. Mean glycosylated haemoglobin levels (HbAlc%) fell from 11.1±2.0% pre-guar to 10.5 ± 2.2% (P< 0.001) after one month on guar and to 10.1±2.3% ( P<0.0001) after two months. Following discontinuation of guar, HbAlc% rose to 11.1±2.5% ( P<0.002). However, there were no significant changes in fasting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

1986
1986
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 11 publications
1
6
0
Order By: Relevance
“…In this way, Jones et al (1985) found no changes in lipid levels after the administration of this fibre, while other authors obtained significant reductions in LDL cholesterol concentrations without changes in HDL cholesterol (Holamn et al, 1987) or with a significant decrease in total cholesterol (Blake et al, 1997).…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…In this way, Jones et al (1985) found no changes in lipid levels after the administration of this fibre, while other authors obtained significant reductions in LDL cholesterol concentrations without changes in HDL cholesterol (Holamn et al, 1987) or with a significant decrease in total cholesterol (Blake et al, 1997).…”
Section: Discussionmentioning
confidence: 59%
“…The results obtained with other soluble fibres such as guar gum are variable. Thus, Stahl and Berger (1990) found no significant differences in glycosilated haemoglobin after the administration of 15 g of guar gum daily during 3 months; Jones et al (1985), after the administration of 10 g=day during 2 months, obtained a significant fall in GhbA 1c levels, without significant changes in 24 h urinary glucose excretion. Behall (1990) observed that guar gum significantly reduced blood C-peptide concentrations after the administration of 31.7 g fibre per day during 6 months and Holman et al (1987) obtained no significant changes in blood C-peptide and GhbA 1c concentrations after the administration of 15 g=day during 8 weeks.…”
Section: Discussionmentioning
confidence: 96%
“…The range of median intakes of soluble fibre across quintiles of soluble fibre intake in 35 988 middle-aged to elderly North American women was 4-8 g/day . In contrast, long-term intervention studies in which improvement in glycaemic control has been found have provided soluble fibre (guar gum) in quantities of around 10-20 g/day (Aro et al, 1981;Ray et al, 1983;Jones et al, 1985). It is possible to increase soluble fibre intake to this extent from dietary changes.…”
Section: Fibrementioning
confidence: 99%
“…However, there was no significant change in the plasma triglyceride level, as was found in other studies. 8,12,13,15 Moreover, recent reports have also demonstrated a reduction in the ratio of cholesterol to HDL-cholesterol; by preferential effect the guar reduced the total cholesterol but not the HDL-Cholesterol level. 10,14 This would be beneficial in diabetic patients who are prone to suffer from coronary atherosclerosis, since a higher HDL:LDL ratio is believed to protect against coronary artery disease in men.…”
Section: Fpg and Hbal Values Are Shown Inmentioning
confidence: 96%
“…Several later studies showed that guar gum improves both glycemic and blood lipid levels in diabetes. 10,11,[13][14][15][16] Guar is a non-cellulose, soluble dietary fiber that is extracted from the cluster bean. The most effective mode of guar administration is to mix it with food.…”
Section: Fpg and Hbal Values Are Shown Inmentioning
confidence: 99%